2017
DOI: 10.12783/issn.1544-8053/14/1/1
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Characterization of Grounded Bottom Ash from Indian Thermal Power Plant

Abstract: In present work, an attempt has been made to improve the quality of bottom ash for utilization as a pozzolanic material. All samples were crushed and passed through 250 µm sieve to prepare grounded bottom ash. The physio-chemical, mineral and leaching characteristics of original and grounded bottom ash were studied. Results show that specific gravity and bulk density of all sample increases whereas porosity, water holding capacity and loss of ignition decreases after the grounding the bottom ash. Pozzolanic pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…From leaching results, it was found that concentration of traced elements Co, Mo, and Zn show follows the prescribed limits of drinking water whereas Cr, Cu, Fe, Mg, Mn, Ni, and Pb were found over the prescribed limits. The possible health issues causes due to the leaching of these elements in drinking water are liver failure, lung tumors, nerves system damage and heart attack (Ugurlu 2004;Singh et al 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…From leaching results, it was found that concentration of traced elements Co, Mo, and Zn show follows the prescribed limits of drinking water whereas Cr, Cu, Fe, Mg, Mn, Ni, and Pb were found over the prescribed limits. The possible health issues causes due to the leaching of these elements in drinking water are liver failure, lung tumors, nerves system damage and heart attack (Ugurlu 2004;Singh et al 2017).…”
Section: Resultsmentioning
confidence: 99%
“…The leaching of large amounts of toxic elements in soil and water causes negative effects on the ecosystem (Hower et al 2006). The mobility of traced elements from coal ash pollutes the water sources and cause health hazards (Singh et al 2017). Popovic and Djordjevic (2009) have found that elements like Cr, Ni, Mo, and V show a minimum effect on the environment.…”
mentioning
confidence: 99%
“…Country Bottom Ash Generation (tonnes yr -1 ) USA [6] 10 million Europe [7] 19 million China [8] About 60 million India [9] 100 million Catalonia, Spain [10] thousand Table 2 Information on industrial production capacity [12] Types of Industry…”
Section: Table Bottom Ash Productionmentioning
confidence: 99%
“…They concluded that leachate concentration of trace elements depends upon pH and the L/S ratio. Singh et al (2017b) investigated leaching behavior of fly ash disposal from an Indian thermal power plant. They reported that as the solid concentration of fly ash slurry suspension increases the pH value was decreased.…”
Section: Introductionmentioning
confidence: 99%